Effect of low-level laser therapy on odontoblast-like cells exposed to bleaching agent - Lima, Adriano Fonseca; Ribeiro, Ana Paula Dias; Basso, Fernanda Gonçalves; Bagnato, Vanderlei Salvador; Hebling, Josimeri [UNESP]; Marchi, Giselle Maria; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2013)
The aim of the present study was to evaluate the effect of low-level laser therapy (LLLT) on odontoblast-like MDPC-23 cells exposed to carbamide peroxide (CP 0.01 %-2.21 μg/mL of H2O2). The cells were seeded in sterile 24-well plates for 72 h. Eight groups were established according to the exposure or not to the bleaching agents and the laser energy doses tested (0, 4, 10, and 15 J/cm2). After exposing the cells to 0.01 % CP for 1 h, this bleaching solution was replaced by fresh culture medium. The cells were then irradiated (three sections) with a near-infrared diode laser (InGaAsP-780 ± 3 nm, 40 mW), with intervals of 24 h. The 0.01 % CP solution caused statistically significant reductions in cell metabolism and alkaline phosphate (ALP) activity when compared with those of the groups not exposed to the bleaching agent. The LLLT did not modulate cell metabolism; however, the dose of 4 J/cm2 increased the ALP activity. It was concluded that 0.01 % CP reduces the MDPC-23 cell metabolism and ALP activity. The LLLT in the parameters tested did not influence the cell metabolism of the cultured cells; nevertheless, the laser dose of 4 J/cm2 increases the ALP activity in groups both with and without exposure to the bleaching agent. © 2013 Springer-Verlag London.
Keywords: Alkaline phosphatase; Bleaching treatment; Laser; Low-level laser therapy; Odontoblasts